2007
DOI: 10.1097/mao.0b013e318030d384
|View full text |Cite
|
Sign up to set email alerts
|

A Longitudinal Study on Pediatric Myringoplasty

Abstract: There was no evidence that age influenced surgical outcome in pediatric myringoplasty. Although the graft take rate was more than 80%, true success was only found in two thirds of cases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
45
1
2

Year Published

2011
2011
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(55 citation statements)
references
References 8 publications
7
45
1
2
Order By: Relevance
“…We believe that the high anatomical failure rates at 2 years are no longer solely related to the surgery, and that extrinsic factors to the myringoplasty come to play after 12 months of postoperative follow-up. Our results parallel favourably with recently published studies [8,9,[11][12][13][14][15]. We believe that it is important to standardize the criteria of anatomical success in order to be able to critically compare published results.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…We believe that the high anatomical failure rates at 2 years are no longer solely related to the surgery, and that extrinsic factors to the myringoplasty come to play after 12 months of postoperative follow-up. Our results parallel favourably with recently published studies [8,9,[11][12][13][14][15]. We believe that it is important to standardize the criteria of anatomical success in order to be able to critically compare published results.…”
Section: Discussionsupporting
confidence: 90%
“…They defined successful myringoplasties as ones in which ears that presented intact tympanic membranes with no evidence of otitis media with effusion (OME), cholesteatoma or high negative pressure within a 12-24 month follow-up period. Two decades later, Yung et al [9] reported a similarly reduced success rate of 63% when stricter criteria of intact tympanic membrane with no evidence of OME, atelectasis, discharge, myringitis and stability of hearing were applied. In the last decade, anatomical success rates for pediatric myringoplasty have been reported between 59% [10] and 95% [8].…”
Section: Discussionmentioning
confidence: 99%
“…Age is often cited as a key prognostic factor in evaluation for tympanoplasty in children [15,19,22,23].…”
Section: Discussionmentioning
confidence: 99%
“…Many factors may influence the surgical outcome of tympanoplasty in children, such as age, the size and location of perforation, status of the operated and contralateral ear, www.elsevier.com/locate/anl Auris Nasus Larynx 38 (2011) [21][22][23][24][25] presence of hypertrophic adenoids, function of the auditory tube and surgeons' experience [10,15,17].…”
Section: Introductionmentioning
confidence: 99%
“…Kumar et al [20] in a retrospected study published 2010 reported the results of 132 tympanoplasties performed in children ranging from 6-15 years, no statistical significant difference between age and successful result were found. On the other hand, Gupta and Mishra [8], Lin and Messner [21] and Yung et al [22] reported that age is a key prognostic factor in evaluation for tympanoplasty in children.…”
Section: Patient Agementioning
confidence: 99%